Legal Protection for Patients of Online Healthcare Service: Analysis of Risks and Challenges of Healthcare Services in Digital Era - Purnomo, Hadi (Sekolah Tinggi Ilmu Kepolisian, 2025)
The use of online healthcare services has the potential to generate various legal issues. The formulation of the problem in this research is how legal protection for patients in online healthcare services is provided, what risks and challenges are faced in providing legal protection for patients in healthcare services in the digital era, and how health law should adapt to the development of digital technology. This research employs a normative legal research method. The research findings show that legal protection for patients in online healthcare services is crucial to ensure that patients' rights are protected in the rapidly evolving digital era. Based on Philipus M. Hadjon's theory of legal protection, both preventive and repressive legal protections must be applied synergistically in the regulation of online healthcare services. Although digital healthcare services offer many benefits, such as easier and faster access, there are significant risks and challenges in providing legal protection for patients. The legal vacuum concerning regulations on telemedicine, the potential misuse of personal data, the limitations of service quality standards, and the lack of effective supervision are major issues that need to be addressed immediately. Furthermore, issues in dispute resolution between patients and online healthcare providers also worsen the situation. Health law must adapt to the rapid development of digital technology to ensure adequate protection for patients and maintain the quality and fairness of healthcare services. This legal adaptation is essential in regulating telemedicine practices, ensuring ethical and professional standards for medical personnel providing digital services, and protecting patients' personal data from potential misuse or breaches. Therefore, health law must balance technological innovation and the protection of patients' fundamental rights, creating a legal framework that is adaptive and responsive, enabling the healthcare sector to develop safely and fairly in the digital era.